2012
DOI: 10.1093/occmed/kqs111
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of occupational asthma due to chromium and cobalt

Abstract: Chromium salt and cobalt can be responsible for OA and OR in workers exposed to MWF aerosols. Onset of symptoms in those with positive specific challenges followed change in MWF brand. Workers with OA had increased urinary concentrations of chromium and cobalt, and those with OR had increased urinary concentrations of chromium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…Each of these substances can result in nasal symptoms and contact dermatitis, both irritant and allergic [Gheysens et al 1985;Burton et al 2012;Walters et al 2012]. The results of our exposure assessment, medical interviews, and analysis of the health questionnaire suggest that cobalt dust exposure was a likely cause of nasal, respiratory, and skin symptoms reported by femoral finishers.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Each of these substances can result in nasal symptoms and contact dermatitis, both irritant and allergic [Gheysens et al 1985;Burton et al 2012;Walters et al 2012]. The results of our exposure assessment, medical interviews, and analysis of the health questionnaire suggest that cobalt dust exposure was a likely cause of nasal, respiratory, and skin symptoms reported by femoral finishers.…”
Section: Discussionmentioning
confidence: 74%
“…However, machinists could have cobalt and chromium exposure from the tungsten carbide machining tools. Studies have found that machining with these tools can potentially leach cobalt and chromium into MWFs [Sjogren et al 1980;Walters et al 2012], which can be inhaled via MWF mist or contacted through skin contamination. Our results for cobalt and chromium in used MWF samples were consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobalt has been found to produce tumors in animals and is likely a human carcinogen as well. Occupational exposure to cobalt powder has been linked to vision, asthma and hearing problems [41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study conducted by Walters et al, (2012) set out to determine the extent of an outbreak of OA in a machining plant that used MWF. This study was instigated after five employees were referred to the Chest Clinic, Birmingham.…”
Section: Background and Aimsmentioning
confidence: 99%